One hundred years of catholic moral theology: Continuities and changes - Ryan, Thomas (The Australasian Catholic record, 2023)
Some years ago, an elderly Marist, the late Fr James Bell, SM, made a comment that came to mind as I was preparing this article. He was ordained in 1925, after his studies at the Marist seminary located in Hawkes Bay, New Zealand. We were discussing those years and the impact of modernism, Pius X's encyclical Pascendi (1907), and the subsequent anti-modernist oath required of all ordained ministers, seminary professors, and religious superiors.